PANDUAN UNGGAH MANDIRI KARYA ILMIAH: Tinjauan Atas Pelaksanaan Pencatatan Belanja Honorarium Pegawai Non PNSD Dalam Realisasi Anggaran Badan Keuangan Daerah Kota Depok - Nurul Kusumawardhani (2021)
This Final Project Report is carried out at Badan Keuangan Daerah Kota Depok which is located at Government Office Dibaleka Building II, Margonda Raya No. 54, Depok West Java 16431. Badan Keuangan Daerah Kota Depok is a regional government agency as a budget user to assist government affairs. The purpose of this Final Project Report is to review the implementation of cash based recording of the Non Civil Servant Honorarium in budget realization, apart from that there are documents who used as evidence of cash disbursements for expenditures that have been made for 1 (one) year. The recorded will be stored in the Regional Financial Reporting Information System (SIPKD) who managed by the assistant Expenditure Treasurer.